EFEKTIVITAS DAN KEMANDIRIAN KEUANGAN DAERAH OTONOM KABUPATEN/KOTA DI PROPINSI BALI TAHUN 2002 – 2006 - DWIRANDRA, A.A.N.B. (Jurnal Ilmiah Akuntansi dan Bisnis, 2008)
This research aims to assess performance of financial independency and effectiveness of autonomous regencies/city in Province of Bali during the year of 2002 till 2006 as well as the development trend in the future. This study is a variation of previous studies that specifically related to the uniqueness of Bali as a tourist destination. This characteristic differentiates Bali from other areas because it is fragile to the impact of social, politic, safety and international relation issues. The data sourcing from regional budget of each regencies and city in Bali are analyzed using non statistic techniques consisting of financial ratios and trends analysis.The results show that financial effectiveness of the nine regions in Bali are relatively stable and effective, even some are very effective, meaning that the regions successfully implement the budget. However, the financial independencies are still low for 6 regions, but the remaining 3 are in good level (Badung, Denpasar, and Gianyar). The trend of independency is as follows: Jembrana is the best, followed by Tabanan, Gianyar, and Badung (good), and the rest 5 regions tend to decrease from performance of 2002.
Keywords: financial independency, financial effectiveness, own resources revenue, general allocated fund, regional budget